POTENSI DAN STRATEGI PENGEMBANGAN TAMAN HUTAN RAYA (TAHURA) NGURAH RAI SEBAGAI PRODUK EKOWISATA - Brahma Widhi Christiani; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2014)
ABSTRACT Tahura Ngurah Rai mangrove forest development is an area that offers the potential beauty of wildlife and various species of mangrove. Purpose of the study is to examine the potential of Tahura Ngurah Rai and development strategies undertaken by the SWOT analysis approach. Method used is the method of collecting data through observation to the study site and structured interviews with managers Tahura Ngurah Rai. Data analysis method using qualitative analysis deskriptid. Results from this research that the potential is on offer in Tahura Ngurah Rai is the potential landscape and scenery that includes mangrove forests and rivers are long, which will lead to Teluk Benoa. potential diversity of mangrove species, have 46 types including 27 species of mangrove-dominated families and types true mangrove species ( sonneratia alba, rhizophora apiculata, avicennia marina, aegiceras corniculatum), and socio-cultural potential that exists around the region Tahura Ngurah Rai is the number of places of worship (sacred) which provide opportunities Tahura Ngurah Rai spiritual tourists.